PENGEMBANGAN LAGU ANAK BERBASIS NILAI KARAKTER RELIGIUS BAGI SISWA SEKOLAH DASAR - Engga Dallion. EW; Juhana Sakmal; Petrus Paulus Mbette Suhendro; Rizqa Ekaputri Nurhapsari; Ernes Eka Putri Aritonang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study is intended to develop children's songs based on religious characters for elementary school students. The research method used is Research & Development with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). This study produced two songs entitled "Negeriku Yang Indah" and "Alam Semesta". Based on the validation test of music experts on the songs developed, the percentage score was 88.24% (Very Eligible). The validation test of the class teacher got a score of 89.09% (Very Eligible). Furthermore, the research subjects were fourth grade students of SDN Manggarai 01 Pagi, South Jakarta as respondents. Student response test through three stages, namely One to One (3 respondents), Small Group (6 respondents), and Field Test (20 Respondents), obtained an average score of 83.7% (Eligible). The development of the resulting song can be said to be an Eligible educational media. Therefore, the development of children's songs based on characters needs to be further developed.